2021
DOI: 10.3390/met11020185
|View full text |Cite
|
Sign up to set email alerts
|

Laser Powder Bed Fusion Processing of Fe-Mn-Al-Ni Shape Memory Alloy—On the Effect of Elevated Platform Temperatures

Abstract: In order to overcome constraints related to crack formation during additive processing (laser powder bed fusion, L-BPF) of Fe-Mn-Al-Ni, the potential of high-temperature L-PBF processing was investigated in the present study. The effect of the process parameters on crack formation, grain structure, and phase distribution in the as-built condition, as well as in the course of cyclic heat treatment was examined by microstructural analysis. Optimized processing parameters were applied to fabricate cylindrical sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Evaporation of alloying elements, especially of manganese, due to welding processes of high manganese steels was reported in numerous studies. In particular for additive manufacturing of Fe-34Mn-15Al-7.5Ni-at.% [48] and Fe-17Mn-5Si-10Cr-4Ni-1(V,C)-wt.% [49] by laser powder bed fusion high losses of manganese are reported. Moreover, Gu ¨nther et al [50] show significant evaporation of manganese with increasing energy input during electron beam melting of Cr-Mn-Ni TRIP steel.…”
Section: Resultsmentioning
confidence: 99%
“…Evaporation of alloying elements, especially of manganese, due to welding processes of high manganese steels was reported in numerous studies. In particular for additive manufacturing of Fe-34Mn-15Al-7.5Ni-at.% [48] and Fe-17Mn-5Si-10Cr-4Ni-1(V,C)-wt.% [49] by laser powder bed fusion high losses of manganese are reported. Moreover, Gu ¨nther et al [50] show significant evaporation of manganese with increasing energy input during electron beam melting of Cr-Mn-Ni TRIP steel.…”
Section: Resultsmentioning
confidence: 99%
“…These advantages can be used for a range of applications, such as medical implants, aerospace components, and automotive parts. The improved shape memory properties make the alloys more durable and reliable for these applications [177][178][179][180][181].…”
Section: Intrinsic Methods: Tailoring the Microstructurementioning
confidence: 99%
“…SMAs are not an exception and such techniques have attracted a great deal of interest, although crack formation is still the main challenge. Against this background and paying attention to the latest developments, Ewald et al [5] innovatively applied laser powder bed fusion to produce crack-free samples of a low-cost Fe-based SMA and achieved a good shape recovery by means of an optimized heat treatment route. Applying a different approach to achieve optimized materials, Brailovski et al [6] demonstrated that simulation-driven processing maps can be used to relate the main laser powder bed fusion parameters to the control of density and grain structure of superelastic Ti-18Zr-14Nb alloys.…”
Section: Contributionsmentioning
confidence: 99%